Kajian filosofi dan spiritualitas dalam pengelolaan ekonomi syariah: Pendekatan teosofi - Nabilla, Nabilla (Maliki Interdisciplinary Journal, 2024)
The management of Sharia economics has become a primary focus in global economic discussions, not only as an alternative to conventional systems but also as a model based on the principles of justice, balance, and blessings. However, in efforts to understand the true essence of Sharia economics, the philosophical and spiritual aspects must also be seriously considered. This article explores the philosophical and spiritual study in the management of Sharia economics, with theosophical approaches as the main analytical foundation. We explain the basic concepts of Sharia economics, highlight the underlying philosophies, and delve into the role of spirituality in Sharia economic practices. Additionally, we discuss theosophical approaches in understanding the complex relationship between humans, nature, and God in the context of Sharia economics. By integrating the philosophical and spiritual aspects through a theosophical approach, this article aims to provide deeper insights into high-quality and impactful Sharia economic management.